The Pet Attachment Affects The Person's Mental Condition - Feng, Kewen (Transactions on Materials, Biotechnology and Life Sciences, 2024)
People are more willing to have pets in current society. The interaction with pets brings pet attachment to owners. Studies try to find the benefits of the pet; the pet attachment is the measurable variable to evaluate the benefits and function of the pet. The essay discusses the emotional support of pets by dividing it into positive and negative emotional conditions. Each condition introduces two studies to develop the benefits of pets. In the positive emotion condition, the studies show that different kinds of companion animals can increase the owners' well-being. The study also figures out that the interaction with and presence of pets contribute to the positive mood of the owners. In negative emotion, two studies studied two periods, which bring long-lasting stress and negatively impact people's mental health. The result shows that companion animals can display the function of buffering negative impacts and promoting positive moods. The studies mainly take surveys to measure the data from the participants. Studies conclude that pet attachment to companion animals has emotional support and positively impacts mental health in daily life.